Evaluation of the American Heart Association 2015 revised Jones criteria versus existing guidelines. Issue 1 (29th February 2016) - Kumar, Dinesh; Bhutia, Euden; Kumar, Pradeep; Shankar, Binoy; Juneja, Atul; Chandelia, Sudha
Abstract : Objectives: To compare the diagnostic yield of acute rheumatic fever (ARF) by the American Heart Association/ American College of Cardiology (AHA/ACC) 2015 revised Jones criteria with the WHO 2004 and Australian guidelines 2012. Methods: Retrospective observational study in 93 cases of suspected ARF admitted to the Division of Paediatric Cardiology between January 2012 and December 2014. WHO 2004, Australian guidelines and AHA/ACC 2015 Jones criteria were applied to assess definite and probable ARF. Results: Of the 93 cases, 50 were diagnosed as the first episode of ARF and 43 as a recurrence of the condition. Subclinical carditis was a predominant presentation (38%) in the first episode group (p<0.01) whereas in the recurrence group carditis (88%) was the main presentation (p<0.01). Among the joint manifestations, the majority of patients in both the first episode group and the recurrence group presented with arthralgia. Of all the patients with suspected ARF (50), 34% of cases did not fulfil the standard Jones criteria 2004; however, 86% qualified as having ARF on applying the Australian and AHA/ACC 2015 criteria. Surprisingly in the recurrence group only 67% of the patients fulfilled AHA/ACC 2015 despite the modifications incorporated beyond WHO 2004; however, all the patients fulfilled the Australian guidelines either as definite (88.4%) or probable (11.6%). Inclusion of subclinical carditis, polyarthralgia and monoarthritis as major criteria influenced the diagnosis to definite ARF in 20%, 10% and 4% of patients, respectively. Conclusions: The clinical manifestations of ARF, comprising subclinical carditis and arthralgia, are possibly milder in the Indian population; hence, inclusion of subclinical carditis, polyarthralgia and monoarthritis as major criteria in the newer guidelines has improved the diagnostic yield of ARF. In the absence of a gold standard for the diagnosis of ARF, it is not possible to comment on sensitivity and specificity.